Importance of basic research in the academic training of health science students - Penissi, Alicia Beatriz (2021)
There is no doubt that the construction of knowledge in the medical sciences is a complex process in continuous transformation, which is born and develops from the basic sciences. The creation of new knowledge at this level is carried out through scientific research, which is why the participation of students in basic research constitutes an optimal instance of training for their subsequent and gradual integration into clinical, epidemiological or technological research projects.